Laser drilling through Hashma sandstone - Mohamed Hosin ElNeiri; Abdel Sattar Abdel Hamid Dahab; Abdulaziz Mohamed Abdulaziz; Khalid Mahmoud Abdelghany (Petroleum Research)
The application of laser in the drilling and perforation of oil wells can achieve great benefits such as reduced drilling costs and time with a higher rate of penetration (ROP) and elimination of casing necessity in oil and gas well drilling. This paper presents an original experimental investigation of Laser cutting through Hashma sandstone (a common quarry rock in Egypt) to develop a good understanding of the laser cutting process in sandstone. Five blocks of Hashma sandstone with dimensions of 35 cm × 35 cm × 10 cm were utilized to study the effects of the various parameters involved in the lasing (cutting) process in order to evaluate the cutting process through sandstone, investigate the effect of laser parameters on the process and the cutting mechanisms. The experimental results showed that the laser drilling can provide lower specific energy (SE) compared to conventional drilling methods, revealed the effect of various laser and rock parameters (such as beam power, intensity, duration, sample size, and orientation) on the cutting process, and demonstrated the laser cutting mechanisms through sandstone such as thermal spallation and melting mechanisms. Several parameters must be optimized for an optimum laser cutting process with the lowest SE, such as using the optimum beam power, beam duration (or Lasig time), and beam mode (continuous or pulsed). The optimum parameters may change from one case to another and depend on the overall interactions among the various variables such as thermal dissipation rate and purging system efficiency.